Maternity clinic practices and exclusive breastfeeding in Cyprus: BrEaST start in life study - Economou, Mary; Kolokotroni, Ourania; Paphiti-Demetriou, Irene; Lambrinou, Ekaterini; Kouta, Christiana; Hadjigeorgiou, Eleni; Hadjiona, Vasiliki; Tryfonos, Froso; Filippou, E.; Middleton, Nicos (My University, 2017)
While the effectiveness of the Baby-Friendly Hospital (BFH) Initiative’s “Ten Steps for Successful Breastfeeding” has been documented, there is often suboptimal implementation. In Cyprus, there are no BFH and rates of exclusively breastfeeding are low.
Keywords: Baby-Friendly Hospital; Breastfeeding; Exclusive breastfeeding